Oxidized Low‐Density Lipoprotein Induces Macrophage Production of Prothrombotic Microparticles. Issue 15 (4th August 2020) - Marchini, Julio F.; Manica, Andre; Crestani, Paulo; Dutzmann, Jochen; Folco, Eduardo J.; Weber, Heinz; Libby, Peter; Croce, Kevin
Abstract : Background: Activated vascular cells produce submicron prothrombotic and proinflammatory microparticle vesicles. Atherosclerotic plaques contain high levels of microparticles. Plasma microparticle levels increase during acute coronary syndromes and the thrombotic consequences of plaque rupture likely involve macrophage‐derived microparticles (MΦMPs). The activation pathways that promote MΦMP production remain poorly defined. This study tested the hypothesis that signals implicated in atherogenesis also stimulate MΦMP production. Methods and Results: We stimulated human primary MΦs with proinflammatory cytokines and atherogenic lipids, and measured MΦMP production by flow cytometry. Oxidized low‐density lipoprotein (oxLDL; 25 µg/mL) induced MΦMP production in a concentration‐dependent manner (293% increase; P <0.001), and these oxLDL MΦMP stimulatory effects were mediated by CD36. OxLDL stimulation increased MΦMP tissue factor content by 78% ( P <0.05), and oxLDL‐induced MΦMP production correlated with activation of caspase 3/7 signaling pathways. Salvionolic acid B, a CD36 inhibitor and a CD36 inhibitor antibody reduced oxLDL‐induced MΦMP by 67% and 60%, respectively. Caspase 3/7 inhibition reduced MΦMP release by 52% ( P <0.01) and caspase 3/7 activation increased MΦMP production by 208% ( P <0.01). Mevastatin pretreatment (10 µM) decreased oxLDL‐induced caspase 3/7 activation and attenuated oxLDL‐stimulated MΦMP production and tissue factor content by 60% ( P <0.01) and 43% ( P <0.05), respectively. Conclusions: OxLDL induces the production of prothrombotic microparticles in macrophages. This process depends on caspases 3 and 7 and CD36 and is inhibited by mevastatin pretreatment. These findings link atherogenic signaling pathways, inflammation, and plaque thrombogenicity and identify a novel potential mechanism for antithrombotic effects of statins independent of LDL lowering.